Physical and coordinative predictors of 50-m freestyle swimming performance among male students - Ahmad Yeri Sulistianto; Kamal Firdaus; Umar Umar; Nuridin Widya Pranoto (Journal of Educational and Learning Studies, 2026)
This study aimed to examine the direct and indirect effects of arm muscle strength, leg muscle explosive power, and hand–eye coordination on 50-m freestyle swimming speed among students of the Pandu Mahawira Swimming Guidance Program, Padang. This quantitative study employed a path analysis design involving 30 male students selected through purposive sampling. Data were collected using a hand grip dynamometer, Vertical Jump Test, Hand Wall Toss Test, and a 50-m freestyle swimming test. The data were analyzed using descriptive statistics and path analysis. Arm muscle strength contributed 24.20%, leg muscle explosive power 7.30%, and hand–eye coordination 6.40% to swimming speed. Through mediation by hand–eye coordination, the total contributions of arm muscle strength and leg muscle explosive power increased to 26.03% and 17.28%, respectively. Collectively, the predictors explained 77.8% of the variance in swimming performance. Arm muscle strength, leg muscle explosive power, and hand–eye coordination are significant determinants of 50-m freestyle swimming speed and should be developed simultaneously to optimize sprint swimming performance.